Autoimmune polyendocrine syndrome type 3 in a multiple sclerosis patient. Issue 3 (20th July 2015) - Masuda, Saeko; Mori, Masahiro; Hamada, Shinsuke; Masuda, Hiroki; Uzawa, Akiyuki; Kuwabara, Satoshi
Abstract Autoimmune polyendocrine syndromes (APS), a group of autoimmune‐mediated multiple endocrine gland failure, type 3 is composed of autoimmune thyroid disease with endocrinopathy, including type 1 diabetes mellitus (DM), other than adrenal insufficiency. Only a few cases of multiple sclerosis (MS) with APS type 3 have been reported. We present the case of a 37‐year‐old Japanese man diagnosed with MS and Graves' disease at 22 years‐of‐age. Interferon‐β‐1b therapy, which he had previously discontinued for 10 years, was restarted for MS at 35 years‐of‐age. After the therapy, he complained of thirst and rapid bodyweight loss (15 kg/6 months), and developed type 1 DM. At onset of DM and before the restart of interferon‐β‐1b therapy, antiglutamic acid decarboxylase antibody findings had been positive. He was diagnosed as having APS type 3, associated Graves' disease and type 1 DM in addition to MS. Our case suggested that MS can be concomitant with APS type 3, and that interferon‐β‐1b therapy for a MS patient with a specific genetic background could induce onset of type 1 DM.